Rice responses to single application of coated urea on yield, dry matter accumulation, and nitrogen uptake in Southern China. (14th September 2017) - Xin, Yang; Wenhai, Mi; Shaofu, Wu; Lianghuan, Wu; Jianqiu, Chen
ABSTRACT: Nitrogen is the most important element for rice ( Oryza sativa L.) growth. However, excessive use of conventional urea leads to serious environmental problems in China. The objective of this study was to evaluate the release patterns of coated urea and response of rice to coated urea on dry matter accumulation, nitrogen uptake, and nitrogen use efficiencies on a clay soil. A two single-year experiment was carried out in southern China to evaluate two coated urea, polymer-coated urea (PCU) and polymer-sulfur coated urea (PSCU). Nitrogen (N) release patterns of PCU and PSCU were determined in the laboratory and in the field. The release rate of PSCU in the field was much higher than that in the laboratory. And PCU had a similar release pattern both in the field and laboratory. Compared with urea, rice fertilized with PCU and PSCU had similar dry matter accumulation, but higher grain yield and N use efficiencies. Recovery efficiency of PCU treatment reached 50% in 2012 and 60% in 2013, around 40% for PSCU, which was only 16% for single application of urea.